Prevalence of Insomnia and Factors Associated with it Among the Elderly People of Sarangdanda VDC in Panchthar District - Subedi, Raj Kumar (Dhaulagiri Journal of Sociology and Anthropology, 2011)
Insomnia is one of the major and unsolved problems in older people. Most of the sleep studies report that the different forms of insomnia like Difficulty Initiating Sleep (DIS), Difficulty Maintaining Sleep (DMS) and Non-Restorative Sleep (NRS) are common among the elderly that are associated to many factors. The objective of the study was to measure the prevalence of insomnia and the factors associated to it among the elderly people. A cross-sectional study was conducted among 142 elderly people of and above 60 years of age in Sarangdanda VDC of Panchthar District of Eastern Nepal. The presence or absence of insomnia and the associated factors were assessed on them by the help of interview schedule. The results were analyzed using chi-square test in SPSS (version 11.5). DMS was the most common reported form of insomnia among the elderly followed by DIS and NRS. Association between insomnia and each of factors like use of tobacco before sleeping hours, eating too close to bedtime, use of tea/coffee before sleeping hours and use of alcohol before sleeping hours were statistically significant at 95% level of confidence. Insomnia affects a large proportion of elderly and is triggered by many factors like use of tobacco before sleeping hours, use of tea/coffee before sleeping hours, eating too close to bedtime and use of alcohol before sleeping hours. Keywords: Alcohol; tea/coffee; difficulty initiating sleep (DIS); difficulty maintaining sleep (DMS); non-restorative sleep (NRS); tobacco DOI: 10.3126/dsaj.v4i0.4517 Dhaulagiri Journal of Sociology and Anthropology Vol.4 2010 pp.129-142